2006
DOI: 10.1108/02621710610678481
|View full text |Cite
|
Sign up to set email alerts
|

Working on the positive emotional attractor through training in health care

Abstract: PurposeThe aim of this paper is to link complexity theory to the intentional change process by examining the role of emotional attraction. A research study currently underway on intentional change theory (ICT) in a healthcare context is presented.Design/methodology/approachThis paper uses the concept of “attractors” from complexity theory to suggest that emotion affects the process of intentional change in different ways dependent upon whether the emotion is positive or negative. Determination of the emotion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 67 publications
(60 reference statements)
0
11
0
2
Order By: Relevance
“…It is even suggested that formation of learning goals or learning-oriented goals builds from this attractor and results in more successful change. The papers by Dyck et al (2006) and Howard (2006) in this issue explain this dynamic more. But another attractor is also at play in the system -the negative emotional attractor (NEA).…”
Section: Self-organizing and The Pull Of Two Attractorsmentioning
confidence: 96%
“…It is even suggested that formation of learning goals or learning-oriented goals builds from this attractor and results in more successful change. The papers by Dyck et al (2006) and Howard (2006) in this issue explain this dynamic more. But another attractor is also at play in the system -the negative emotional attractor (NEA).…”
Section: Self-organizing and The Pull Of Two Attractorsmentioning
confidence: 96%
“…It is possible that the effects of such subtle changes emerge gradually over time as the person‐system evolves and adapts to illness. For example, Dyck et al (2006) have proposed the notion of ‘emotional attraction’. Activation of positive emotion has been shown to exert a favourable effect on cognition, intention and physiology, whereas negative emotion has been shown to have adverse effects.…”
Section: Mods and Critical Care As A Complex Non‐linear Adaptive Systmentioning
confidence: 99%
“…Although caring stimuli that increase positive emotion and/or decrease negative emotion do not address the pathophysiology of MODS per se , nonetheless, according to the principles of complexity they may ultimately direct the person‐system towards survival. If we acknowledge the system person as a complex adaptive system capable of self‐organization, then subtle actions may be more appropriate to let the system change itself, and to let direction arise by ‘gradually shifting time and attention towards those things that seem to be working’ (Dyck et al , 2006). Indeed, Golbin and Umantsev (2006), through an analysis of different cases of human disorders with complex dynamics concluded that adaptive disorders with chaotic symptoms (such as MODS) should not be aggressively treated, if over‐treated the whole organism may lead to chronic disease or even death.…”
Section: Mods and Critical Care As A Complex Non‐linear Adaptive Systmentioning
confidence: 99%
“…22 The characteristics of these are shown in Table 2. By accessing patients' hopes, dreams, possibilities, and strengths or in effect their ideal self, the PEA condition is created.…”
Section: Role Of Resonance and Dissonancementioning
confidence: 99%
“…Dissonance is expressed by the negative emotional attractor (NEA) and consists of the gaps between patients' ideal and real self or their fears, problems, and shortfalls. 22 This paper explains that the asymmetrical relationship should favour resonance over dissonance to facilitate an effective physician-patient relationship. Specifi cally, this paper examines the positive and negative emotional attractors created by physicians and their respective infl uence on effective communication during diagnostic encounters with patients.…”
Section: Introductionmentioning
confidence: 99%